Can Kindergarten Meals Improve the Daily Intake of Vegetables, Whole Grains, and Nuts among Preschool Children? A Randomized Controlled Evaluation - Berlic, Maja; Battelino, Tadej; Korošec, Mojca (Nutrients, 2023)
Surveys have indicated that preschool children do not consume adequate amounts of vegetables, fruits, whole grains, and nuts. This cross-sectional intervention study aimed to investigate whether a meticulously crafted meal plan for children of kindergarten age (5–6 years) could effectively enhance their daily intake of nutritious foods. Ninety-four healthy children from six kindergartens were enrolled in the study and were randomly assigned to a prototype group (PG) and a control group (CG). The PG kindergartens (n = 4) received a prototype 5-day meal plan that included regulated portions of vegetables, fruits, whole grains, and nuts adhering to dietary guidelines. Conversely, the CG kindergartens (n = 2) adhered to their standard meal plan. Participants maintained their usual eating habits outside of kindergarten and during weekends. Using the dietary assessment tool Open Platform for Clinical Nutrition (OPEN), combined with a 7-day dietary record of food consumed inside and outside the kindergarten, the average daily intake of specific food groups was assessed and compared with the Dietary Guidelines for Children. A total of 57 participants completed the study, 40 from the PG and 17 from the CG. Among the PG participants, the average daily intake of vegetables, whole grains, and nuts compared with the guideline recommendations was significantly higher than in the CG. Notably, only meals consumed within the kindergarten setting significantly improved the overall intake, with the outside intake having no significant effect. This study underscores the vital role of a well-designed and precisely executed meal plan in kindergartens in improving children’s intake of healthy foods. The findings could help drive positive changes in child nutrition within educational environments.